A new species and new records of gasteroid fungi (Basidiomycota) from Central Amazonia, Brazil - Cabral, Tiara Sousa; Silva, Bianca Denise Barbosa; Ishikawa, Noemia Kazue; Alfredo, Donis Da Silva; Neto, Ricardo Braga; Clement, Charles Roland; Baseia, Iuri Goulart (Phytotaxa, 2014)
A new species, Geastrum inpaense, is described morphologically and molecularly. Geastrum lloydianum, G. schweinitzii, Phallus merulinus and Staheliomyces cinctus are reported here as new records for Central Amazonia. In addition, Mutinus fleischeri is reported as a new record for the Americas and Phallus atrovolvatus, as a new record for Brazil.